Competition law and antitrust : a global guide - Gerber, David J. (Oxford : Oxford University Press, 2020)
Competition law now affects virtually all aspects of economic life in many parts of the world. This text provides an overview of competition law's substantive content and methods as well as an analysis of its dynamics. It is a critical tool for anyone dealing with competition law.
This edition also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on September 9, 2020).
Keywords: Antitrust law; Antitrust law (International law)